Non-linear aeroelasticity: An approach to compute the response of three-blade large-scale horizontal-axis wind turbines - Gebhardt, Cristian Guillermo (2014)
In this work, we present an aeroelastic model intended for three-blade large-scale horizontal-axis wind turbines. This model results from the coupling of an existing aerodynamic model and a structural model based on a segregated formulation derived in an index-based notation that enables combining very different descriptions such as rigid-body dynamics, assumed-modes techniques and finite element methods. The developed structural model comprises a supporting tower, a nacelle, which contains the electrical generator, power electronics and control systems, a hub in which the blades are connected to a rotating shaft, and three blades, which extract energy from the wind. Flexible blades are discretized into beam finite elements and the flexible tower is discretized into assumed modes. The nacelle and hub are considered rigid. To illustrate the flexibility of the structural modeling, the tower, nacelle and hub are modeled as a single kinematic chain and each blade is modeled separately. To establish the blade-hub attachments, we use constraint equations. Thus, the resulting equations are differential algebraic. We also expose a general procedure for connecting the non-matching structural and aerodynamic meshes. Finally, we present results, some of them are validations, which prove that our new approach is reliable and does have capability to capture non-linear phenomena such as centrifugal stiffening, flutter and large yaw errors, and the remaining ones correspond to the aeroelastic response of a wind turbine during a start-up maneuvering.